Effects of a phase change cooling garment during exercise in the heat. Issue 8 (14th September 2017) - Butts, Cory L.; Torretta, Madeline L.; Smith, Cody R.; Petway, Adam J.; McDermott, Brendon P.
Abstract: The purpose of our study was to examine the physiological, perceptual, and performance effects of wearing a phase change cooling garment (CG) during an interval exercise routine in the heat. Sixteen male participants (age 23 ± 3 years, ht 1.76 ± 0.11 m; wt 78.5 ± 11.2 kg; body fat 15.2 ± 5.8%) completed two trials (one with phase change inserts, CG, and one control without inserts) consisting of two submaximal exercise portions separated by 5-minute seated rest, and a final maximal effort performance bout. Each submaximal bout involved 30 seconds or 1 minute of muscular endurance and agility exercises and 5 minutes of treadmill jogging and step-ups. The performance bout included 30 seconds or 1 minute of muscular endurance and agility exercises, with participants completing as many repetitions as possible, followed by a 15-minute recovery (active and passive). Rectal temperature ( T re ) and heart rate were not different between trials, however change in T re from baseline was improved during 10 and 15 minutes of recovery with the CG ( P  < .05). Mean skin temperature was lower using the CG vs control throughout the trial ( P  < .05). Thermal sensation was lower when using the CG compared to control ( P  < .001). There were no differences in any outcomes of the performance exercises ( P  > .05). These findings indicate that the continuous use of a CG during an interval style workout in the heat provides improvements in thermal sensation, however, only minimal thermophysiological benefits, and no performance augmentation.